Population Structure Based on Microsatellite Length Polymorphism, Antifungal Susceptibility Profile, and Enzymatic Activity of Candida auris Clinical Isolates in Russia - Ellina Oganesyan; Victoria Klimenteva; Irina Vybornova; Valentina Venchakova; Ekaterina Parshikova; Sergey Kovyrshin; Olga Orlova; Alexander Kruglov; Svetlana Gordeeva; Natalya Vasilyeva; Anastasiya Taraskina (Journal of Fungi)
Candida auris is an emerging multidrug-resistant fungal pathogen causing nosocomial transmission and invasive infections with high mortality. This study aimed to investigate the genetic relationships, enzymatic activities, and drug-resistance profiles of C. auris isolates to evaluate the population and epidemiological diversity of candidiasis in Russia. A total of 112 clinical isolates of C. auris were analyzed from May 2017 to March 2023 in 18 hospitals across Saint Petersburg, the Leningrad Region, and Moscow. Species identification was confirmed by ITS sequencing, and genotyping was performed using 12 short tandem repeat (STR) markers. Antifungal susceptibility was tested using Sensititre™ YeastOne™ plates, and hydrolytic enzyme production was measured by the plate method. ITS sequencing confirmed that all isolates belonged to a single ITS cluster (clades I and III). Fifteen distinct STR genotypes were identified, with genotype I being dominant (n = 53). The most variable of the analyzed markers turned out to be M3-Ia, which was represented in the Russian population by eight different variants. Fluconazole resistance was found in 111 isolates, 17% were resistant to amphotericin B, and 3.6% to 5-flucytosine. Phospholipase activity was strong in most strains, especially in urine isolates (p = 0.014). Conclusion: The predominance of STR genotype I and its variability at the M3-Ia locus suggest its association with nosocomial outbreaks and transmissibility in Russia.